CHINESE NEW YEAR CANDLE BUSINESS IN TANAH GOCAP TANGERANG - Afifah, Inggrid Nur (Bambuti, 2023)
This article discusses Chinese ethnic culture in Lilin Ong business in Tanah Gocap, Tangerang. The author uses qualitative research methods, namely collecting data from the library, as well as observations and interviews with the owner of Lilin "Ong", namely Mr Antonius. Chinese New Year candles are a work of Chinese ethnicity which is considered a characteristic of cultural traditions and shows Chinese identity in Indonesia. Apart from that, the author also explains the Chinese business culture that Lilin Ong maintains. When carrying out ceremonies in Chinese cultural traditions, food is always offered, and candles are needed to perform the prayer.